x Turn on thread page Beta
 You are Here: Home

# P2 Functions questions! watch

Announcements
1. The function P & Q are defined by:

P:X -------> Ax+B

Q:X -------> Cx+D

Where A,B,C and D are constants, Guven that pq(x)=qp(x), show that:

D(A-1) = B(c-1)

I really got stuck on this one, dunno why, seems simple enough but i dunno...
2. Anyone??????
3. (Original post by KOH)
The function P & Q are defined by:

P:X -------> Ax+B

Q:X -------> Cx+D

Where A,B,C and D are constants, Guven that pq(x)=qp(x), show that:

D(A-1) = B(c-1)

I really got stuck on this one, dunno why, seems simple enough but i dunno...
pq(x) = qp(x) therefore:

A(Cx+D) + B = C(Ax+B) + D
D(A-1)=B(C-1)
4. (Original post by Bhaal85)
pq(x) = qp(x) therefore:

A(Cx+D) + B = C(Ax+B) + D
D(A-1)=B(C-1)

Thnks
5. (Original post by KOH)
Thnks

TSR Support Team

We have a brilliant team of more than 60 Support Team members looking after discussions on The Student Room, helping to make it a fun, safe and useful place to hang out.

This forum is supported by:
Updated: June 4, 2004
Today on TSR

### Loughborough better than Cambridge

Loughborough at number one

### Can I date a girl with no boobs?

Poll

The Student Room, Get Revising and Marked by Teachers are trading names of The Student Room Group Ltd.

Register Number: 04666380 (England and Wales), VAT No. 806 8067 22 Registered Office: International House, Queens Road, Brighton, BN1 3XE